Members of a Novel Class of Arabidopsis Rho Guanine Nucleotide Exchange Factors Control Rho GTPase-Dependent Polar Growth - Gu, Ying (American Society of Plant Biologists, 2006)
Rho family small GTPases are signaling switches controlling many eukaryotic cellular processes. Conversion from the GDP- to GTP-bound form is catalyzed by guanine nucleotide exchange factors (GEFs). Rho GEFs in animals fall into two structurally distinct classes containing DH and DOCKER catalytic domains. Using a plant Rho GTPase (ROP1) as bait in yeast two-hybrid screens, we identified a family of Rho GEFs, named RopGEFs. The Arabidopsis thaliana RopGEF family of 14 members contains a conserved central domain, the domain of unknown function 315 (DUF315), and variable N- and C-terminal regions. In vitro GEF assays show that DUF315 but not the full-length version of RopGEF1 has high GEF activity toward ROP1. Our data suggest that the variable regions of RopGEF1 are involved in regulation of RopGEF through an autoinhibitory mechanism. RopGEF1 overexpression in pollen tubes produced growth depolarization, as does a constitutively active ROP1 mutant. The RopGEF1 overexpression phenotype was suppressed by expression of a dominant-negative mutant of ROP1, probably by trapping RopGEF1. Deletion mutant analysis suggested a requirement of RopGEF activity for the function of RopGEF1 in polar growth. Green fluorescent protein–tagged RopGEF1 was localized to the tip of pollen tubes where ROP1 is activated. These results provide strong evidence that RopGEF1 activates ROP1 in control of polar growth in pollen tubes.